Influence of the Freeze-Drying Process on the Physicochemical and Biological Properties of Pre-heated Amphotericin B Micellar Systems - Siqueira, Scheyla D. V. S.; Silva-Filho, Miguel A.; Silva, Christian A.; Araujo, Ivonete B.; Silva, Acarilia E.; Fernandes-Pedrosa, Matheus F.; Oliveira, Anselmo Gomes de [UNESP]; Egito, E. Socrates T. (Springer, 2014)
The moderate heat treatment of amphotericin B (AmB) in its micellar form (M-AmB) results in superaggregates (H-AmB) that present a substantially lower toxicity and similar activity. The aim of this work was to evaluate the H-AmB behavior after a freeze-drying process. H-AmB and M-AmB micelles were evaluated before and after freeze-drying concerning their physicochemical and biological properties by spectrophotometry and activity/toxicity assay, respectively. Four concentrations of M-AmB and H-AmB were studied aiming to correlate their aggregation state and the respective biological behavior: 50 mg L-1, 5 mg L-1, 0.5 mg L-1, and 0.05 mg L-1. Then, potassium leakage and hemoglobin leakage from red blood cells were used to evaluate the acute and chronic toxicity, respectively. The efficacy of M-AmB and H-AmB formulations was assessed by potassium leakage from Candida albicans and by the broth microdilution method. After heating, in addition to an evident turbidity, a slight blueshift from 327 to 323 nm was also observed at the concentrations of 50 and 5 mg L-1 for H-AmB. Additionally, an increase in the absorbance at 323 nm at the concentration of 0.5 mg L-1 was detected. Concerning the toxicity, H-AmB caused significantly lower hemoglobin leakage than M-AmB. These results were observed for H-AmB before and after freeze-drying. However, there was no difference between H-AmB and M-AmB concerning their activity. Accordingly, the freeze-drying cycle did not show any influence on the behavior of heated formulations, highlighting the suitability of such a method to produce a new AmB product with a long shelf life and with both greater efficiency and less toxicity.
Keywords: activity; amphotericin B; freeze-drying; heating; toxicity